Hyperoside Suppresses Renal Inflammation by Regulating Macrophage Polarization in Mice With Type 2 Diabetes Mellitus - Liu, Jialing; Zhang, Yanmei; Sheng, Hongqin; Liang, Chunling; Liu, Huazhen; Moran Guerrero, Jose Alberto; Lu, Zhaoyu; Mao, Wei; Dai, Zhenhua; Liu, Xusheng; Zhang, Lei (Frontiers in Immunology, 2021)
Accumulating evidence reveals that both inflammation and lymphocyte dysfunction play a vital role in the development of diabetic nephropathy (DN). Hyperoside (HPS) or quercetin-3-O-galactoside is an active flavonoid glycoside mainly found in the Chinese herbal medicine Tu-Si-Zi. Although HPS has a variety of pharmacological effects, including anti-oxidative and anti-apoptotic activities as well as podocyte-protective effects, its underlying anti-inflammatory mechanisms remain unclear. Herein, we investigated the therapeutic effects of HPS on murine DN and the potential mechanisms responsible for its efficacy. We used C57BLKS/6J Lep db/db mice and a high glucose (HG)-induced bone marrow-derived macrophage (BMDM) polarization system to investigate the potentially protective effects of HPS on DN. Our results showed that HPS markedly reduced diabetes-induced albuminuria and glomerular mesangial matrix expansion, accompanied with a significant improvement of fasting blood glucose level, hyperlipidaemia and body weight. Mechanistically, pretreatment with HPS effectively regulated macrophage polarization by shifting proinflammatory M1 macrophages (F4/80+CD11b+CD86+) to anti-inflammatory M2 ones (F4/80+CD11b+CD206+) in vivo and in bone marrow-derived macrophages (BMDMs) in vitro, resulting in the inhibition of renal proinflammatory macrophage infiltration and the reduction in expression of monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor (TNF-α) and inducible nitric oxide synthase (iNOS) while increasing expression of anti-inflammatory cytokine Arg-1 and CD163/CD206 surface molecules. Unexpectedly, pretreatment with HPS suppressed CD4+ T cell proliferation in a coculture model of IL-4-induced M2 macrophages and splenic CD4+ T cells while promoting their differentiation into CD4+IL-4+ Th2 and CD4+Foxp3+ Treg cells. Taken together, we demonstrate that HPS ameliorates murine DN via promoting macrophage polarization from an M1 to M2 phenotype and CD4+ T cell differentiation into Th2 and Treg populations. Our findings may be implicated for the treatment of DN in clinic.